Unlocking Economic Growth: Exploring the Role of Foreign Direct Investment, Idiosyncratic Risk, and Economic Activity - Marselinus Asri; Paulus Tangke; Lukman; Robert Jao (IECON: International Economics and Business Conference, 2025)
This study explores the complex interplay among foreign direct investment (FDI), idiosyncratic risk, inflation, and various economic activities in ASEAN countries. Through regression analysis, the research investigates the impact of these factors on managerial work, economic activity, and overall economic growth within the region. The findings underscore significant associations between FDI, idiosyncratic risk, inflation, and diverse economic activities, offering valuable insights for policymakers and stakeholders seeking to enhance economic development strategies in ASEAN countries.